The Language Attitude and The Language Behavior of Mandar Baruga Community in Tapalang Subdistrict Mamuju District - Dita Mulyana Ramadhani; Ekha Alwiah Haseng (Edumaspul: Jurnal Pendidikan, 2021)
This study aims to describe the language attitude and the language behavior of Mandar Baruga community in Tapalang subdistrict, Mamuju district. The type of this study is classified as a mixed methods research. The data source of this study is Mandar Baruga community in Tapalang subdistrict, Mamuju district. Data this research is the language attitude and the language behavior of Mandar Baruga community in Tapalang subdistrict, Mamuju district. Data collection techniques used were observation, interview, questionnaire, and recording. The results of this study indicated three types of language attitudes, namely 79.94%of loyalty, 89.93% of pride, and 79.26% of awareness. As for the behavior discovered (1) greet the speech partner first, (2) use greeting words, (3) do not decide on their own opinion, (4) pray for the good, (5) respond well, (6) answer politely, (7) be polite in ask questions, (8) act properly without being asked, (9) entertain guests well, (10) be quick to entertain guests, (11) be sensitive, (12) do not take things that do not belong to them, (13) ask questions before acting, (14) ) greet each other, (15) do not be indifferent to their guests, (16) appreciate the gifts of others, (17) praise others, (18) keep promises, and (19) care for others. The impoliteness found, namely (1) does not reflect caring by being indifferent, (2) does not reflect the value of understanding by opposing and refusing, (3) not reflecting the value of freedom by forcing and urging, (4) not reflecting the value of subtlety by speaking loudly. , (5) does not reflect the value of patience by being angry, intimidating, cursing, and insulting, (6) does not reflect the value of making up honesty, (7) does not reflect the value of humility by praising oneself, and (8) does not reflect the value of propriety by nagging. Keywords: community, Mandar, behavior, attitude